2020
DOI: 10.1007/s42380-020-00079-y
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Self-efficacy in Preventing and Intervening in School Bullying: a Systematic Review

Abstract: Self-efficacy, commonly seen as an important competence for teachers when intervening in bullying, is a heterogeneous construct. Differences in the specific kinds of self-efficacy under review, its assessment, theoretical foundations, and the samples used when researching it generate diverse results that can be hard to integrate. This systematic review surveys existing literature on the extent of teachers’ self-efficacy in managing bullying and its connection to the likelihood that teachers will intervene in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 59 publications
1
22
0
Order By: Relevance
“…The positive correlation of TCEB with school climate and principal support, and its negative correlation with bullying rates provide evidence of concurrent validity of the scale. Overall, our findings align with previous research [34,43,[57][58][59], which suggests that teachers' collective efficacy to handle bullying impacts school functioning and student bullying behavior. Specifically, our findings indicate that the quality of school climate influences teachers' collective efficacy.…”
Section: Concurrent Validitysupporting
confidence: 91%
See 3 more Smart Citations
“…The positive correlation of TCEB with school climate and principal support, and its negative correlation with bullying rates provide evidence of concurrent validity of the scale. Overall, our findings align with previous research [34,43,[57][58][59], which suggests that teachers' collective efficacy to handle bullying impacts school functioning and student bullying behavior. Specifically, our findings indicate that the quality of school climate influences teachers' collective efficacy.…”
Section: Concurrent Validitysupporting
confidence: 91%
“…Previous studies suggest that collective teacher efficacy is an essential whole-school factor related to bullying [31][32][33][34][35][36][38][39][40]43]. However, this construct has been scarcely explored in bullying literature [31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Self-efficacy is also a core determinant in many behavioral theories [ 17 ], and essential for explaining teachers’ practices (e.g., [ 18 20 ]). For instance, a recent systematic review showed that teachers with higher self-efficacy intervened in bullying more often than teachers with lower self-efficacy [ 21 ]. Four sources are demonstrated to influence self-efficacy: having successfully performed the task previously, learning vicariously from observing others’ successful performances, being persuaded that one can perform the task, and reducing negative physiological and affective states associated with hesitation.…”
Section: Introductionmentioning
confidence: 99%